Facial Expression and Oral Motoric Exercises to Support Communication in Stroke and Aphasia Patients: A Case Study - Kunoviana, Rizkiyah Diyan; Purwanti, Okti Sri (Sarana Ilmu Indonesia (salnesia), 2025)
Stroke often causes aphasia, a language disorder that hinders verbal and nonverbal communication and reduces the quality of life of patients. This study aims to evaluate the effectiveness of face expression exercises and oral motor exercises in improving face symmetry and communication skills in patients with aphasia stroke. A case study was conducted on two non-hemorrhagic stroke patients with aphasia at Dr. Soehadi Prijonegoro General Hospital in Sragen. The intervention was carried out for three consecutive days, twice a day, in the form of a combination of face expression and oral motor exercises using a mirror. The evaluation was conducted using the Sunnybrook Face Grading System and observation of oral motor function. The results showed an increase in the Sunnybrook score from 40 (grade IV, moderate to severe impairment) to 55 (grade III, mild to moderate) in the first subject, and from 47 (grade III, mild-moderate) to 65 (grade II, near normal) in the second subject. Both experienced an increase in face symmetry, tongue and lip muscle strength, and the ability to pronounce simple words. Face expression exercises and oral motor exercises proved to be effective as a simple, safe, and low-cost intervention to support communication recovery in stroke patients with aphasia.